Supply Chain Systems Performance of Vegetables Commodity to Fulfilled Hotels Demand in Bali - Trinilam, Qurratu Zahrah; Widia, I Wayan; Utama, I Made Supartha (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The vegetable demand supply set by the hotel has standards in the form of quality, on-time, and quantity. Meanwhile, vegetable commodities have a perishable nature whose quality still depends on climate and weather. It is necessary to measure the performance of the vegetable supply chain system. This study aimed to determine the working mechanism and the achievement level of supply chain performance to meet the demand for hotels in Bali. The analysis uses the Food Supply Chain Network (FSCN) framework. The measuring achievement level of performance refers to the Supply Chain Operations Reference (SCOR) method. The object of this study involved the farmers in Bedugul. The results showed that the measuring achievement level of vegetable supply chain performance was in the Perfect Order Fulfillment (POF) matrix of vegetables obtained an average value of 98.2%, considered in the superior category. The Standard Fulfillment (SF) matrix had an average score of 100% (considered in the super categories). Vegetable Flexibility Matrix obtained an average value of 1.2 days (considered superior). The Order Fulfillment Cycle Time (OFCT) matrix had an average value of 0.7 days (considered superior). The Lead Time (LT) matrix also obtained an average value of 0.67 days (considered in the superior class). The Cash to Cash Cycle Time Matrix value of 13,80 days. The measuring achievement level of vegetable supply chain performance is in super performance or the best position.